Best Answer

Since y = 2, 2x + 6y is the same as 2x + 12. Because 2x + 12 = 22, 2x = 10. If 2 Xes are equal to ten, then 1 X is equal to 5.

Q: Y equals 2 2x plus 6y equals 22?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

no

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

2X + 6Y = 12 3X + 9Y = 18 try elimination - 3(2X + 6Y = 12) 2(3X + 9Y = 18) - 6X - 18Y = - 36 6X + 18Y = 36 ================= I will say this system is dependent and an infinite number of solutions can be found.

5x -6y=-30 5x-6y=30 (2x+3y) (2x-3y)=30 4x+6y=30 4x=30 x=30/4

Related questions

6y

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

(2, 1)

it is -4

yes

(3, 3)

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

They are parallel lines.

(3,3)

no

2x plus 6y equals 32 32 divided by 6= 5 R2 5+2= 7x6= 42-5=37-2=35 so X=5